Facial Affect and Interpersonal Affiliation: Displays of Emotion During Relationship Formation in Social Anxiety Disorder - Pearlstein, Sarah L. (Clin Psychol Sci, 2019)
Social anxiety disorder (SAD) often involves difficulty developing relationships. Facial expressions are important in relationship formation, but data are limited regarding facial display production among persons with SAD during social interaction. The current study compared facial displays of individuals diagnosed with SAD (n=41) to control participants (n=24) as they interacted with a confederate; confederates and observers then rated their desire for future interaction with participants. Automated software used the Facial Action Coding System (FACS; Ekman & Friesen, 1978) to classify displays. During portions of the interaction that involved listening to partners, the SAD group smiled less frequently and less intensely than controls, and lower smiling was associated with others’ lower desire for future interaction with participants. Diminished positive facial affect in response to interaction partners may disrupt relationship formation in SAD and may serve as an effective treatment target.